PEMETAAN BARU METODE DAN MODEL PENELITIAN TAFSIR - Umar Zakka; M Thohir (Al-Thiqah : Jurnal Ilmu Keislaman, 2021)
Many researcher of Qur’an and tafsir still making mistake of term in the application of the qur’anic and tafsir researc method. This is because there is no difference between the tafsir method, tafsir research method and tafsir form reasearch. So, the purpose of this research is 2, first to know the definition of tafsir method, tafsir research method and tafsir form research. Second to know the mapping in tafsir method, tafsir research method and tafsir form research. Tafsir method is how to intrepret the verses of the Qur’an, while the tafsir research method is how to interpret the interpretation of mufassir and tafsir form research is format of research. Different of tafsir method and tafsir research method is material object of research. Material object of research in tafsir method is verse of Qur’an and material object of research in tafsir research method is interpretation of mufassir to verses of Qur’an. As for application of method is same, there are 4 ; first from the source aspect is 3 it is: al-ma’thu>r, al-ra’yu and izdiwaj al-mas}a>dir, second from the way of interpretation aspect is 3, it is: baya>niy, muqa>rin, and al-izdiwa>j al-kayfiy, third from breadth of interpretation aspect is 2, it is: it}na>biy and ijma>liy, and fourth from orderly of interpretation aspect is 3, it is: tah}li>liy, mawd}u>’iy and nuzu>liy. Format of tafsir research divided into 4, it is: teks research, ancient script research (philology), living qur’an research, and character research.